WEWNĘTRZNY RYNEK UBEZPIECZEŃ A HARMONIZACJA KONTRAKTU UBEZPIECZENIOWEGO - Brodecki, Zdzisław; Malinowska, Katarzyna (Zeszyty Prawnicze, 2017)
Tendencies on Internal Insurance Market vis a vis Harmonization of European Insurance Contract Law Summary In the paper, the authors describe the main contemporary process which takes place w ithin the insurance contract law in Europe - viz the Euro-merge of private law, as well as the evolution of the insurance contract law during the last decades. The process o f the unification of European private law will also affect the insurance contract law. First of all the impact o f the development o f the ideas shaped in a form of general contract law drafted as the Restatement of the Principles of European Contract Law by the „Lando Group” is undeniable. These rules also applicable to some extent to insurance contracts show that the process of the unification o f insurance contract law cannot be stopped and that it will constantly develop. There can also be observed a process of a specific European com m on law being developed in Europe in different branches, such as product liability, consumer protection, etc. This already influences the harmonization o f the European insurance contract law, and the obstacles to harmonization, existing even ten years ago, have disappeared. The Restatement o f Insurance Contract Law being in preparation by the „Group of Innsbruck” will probably constitute a basis for a future codification o f the insurance contract law.